PERAN BANK RAKYAT INDONESIA (BRI) UNIT KOTA GARO TERHADAP PENINGKATAN USAHATANI KELAPA SAWIT DI DESA TANAH TINGGI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR TAHUN 2014 - Muhammad Ikhwan; Nursiah Chalid; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is conducted in subdistrict of Tapung go downstream camphor regency. Target of this research is conducted to know role of Bank Rakyat Indonesia of unit town of garo to improvement of is effort farmer of oil palm in countryside of highlands of subdistrict of tapung go downstream regency of camphor in the year 2014in this research is methodologies used by quantitative and descriptive with program spss, where sampel used by that is farmer of oil palm borrowing fund in bri, farmer of oil palm which do not borrow fund in bri. to determine sampel use formula slovin,. Technics of data collecting through interview, observation and quetioner.from analyst result of covering clean revenue analysis data, bruto analyst data, total cost analysis, role of Bank Rakyat Indonesia unit of town of garo to improvement of earnings of farmer of oil palm that is equal to rp 117.475.400,- per 2 hectare of per year (12 month) or about rp. 12.070.000,- per month. While net earning from farmer of oil palm which do not borrow fund in bank of BRI that is equal to rp 46.118.640,- per year (12 month) or about rp 3.843.220,- per month. there are difference of net earning of per 2 hectare of per year of equal to rp 71.356.536,- or equal to rp 8.226.780,-per of month.Keywords: Role Of Bank Rakyat Indonesia ( BRI), The Effort Farmer, Agricultural Economy.